Neurocognitive development in HIV-positive children is correlated with plasma viral loads in early childhood. Issue 23 (June 2017) - Weber, Valentin; Radeloff, Daniel; Reimers, Bianca; Salzmann-Manrique, Emilia; Bader, Peter; Schwabe, Dirk; Königs, Christoph
Abstract : Abstract: Because of neurocognitive impairments in perinatally human immunodeficiency virus (HIV)-infected children and adolescents, this study aimed to demonstrate the effect of plasma viral loads and early initiation of sufficient combined antiretroviral therapy (cART) on neurocognitive development. In total, 14 perinatally infected HIV-positive children (median age 8.24 years [range: 6.0–16.74]) receiving lopinavir/ritonavir (LPV/r)-based ART underwent neurocognitive testing using the Wechsler Intelligence Score for Children, 4th Edition (WISC-IV). All 14 patients participated in a pharmacokinetic study in which they were hospitalized for an entire day. As a child's ability to concentrate varies over the course of the day, all tests were performed in the morning. The patients' neurocognitive development did not significantly differ from the normative collective pattern for any of the following composite scores that were examined: full-scale intelligence quotient (IQ) (mean: 106.5, P = .1060), verbal comprehension index (mean: 106.0, P = .1356), perceptual reasoning index (mean: 106.0, P = .1357), working memory index (mean: 106.3, P = .1171), and processing speed index (mean: 98.1, P = .6313). The overall full-scale IQ scores were significantly higher in children who began ART within the first year of life ( P = .0379), whereas low lopinavir/r plasma levels ( P = .0070) and high viral load area under the curves (AUCs) in the first 3 years of life, but not later, significantly correlated with reduced neurocognitive performance (Spearman r 2 = −0.64, P = .0278). In this cohort of cART treated HIV-positive children and adolescents, neurocognitive performance correlated with early and sufficient viral load suppression within the first 3 years of life. Abstract : Supplemental Digital Content is available in the text